Philosophical Perspectives on the Self - Goncalves, Jorge; Goncalves, Jorge; Fonseca, Joao (Peter Lang, 2015)
For the last decade the topic of the Self has been under intense scrutiny from researchers of various areas spanning from philosophy, neurosciences, and psychology to anthropology and sociology. The present volume addresses the Self under different and influent philosophical perspectives: from phenomenology and psychoanalysis to metaphysics and neurophilosophy and discusses several and distinct problems such as personal identity, the core/narrative self-distinction, psychopathologies, the mind-body problem and the nature of the relations between self, consciousness and emotions. The book reflects these different philosophical problems and approaches and aims to provide a map of current philosophical perspectives on the topic of the Self.